2022
DOI: 10.1158/0008-5472.can-20-0371
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of MicroRNA Regulatory Network Architecture and Functional Rerouting in Cancer

Abstract: Somatic mutations are a major source of cancer development, and many driver mutations have been identified in protein coding regions. However, the function of mutations located in microRNAs (miRNAs) and their target binding sites throughout the human genome remains largely unknown. Here, we built detailed cancer-specific miRNA regulatory networks across 30 cancer types to systematically analyze the effect of mutations in miRNAs and their target sites in 3’ UTR, CDS, and 5’ UTR regions. A total of 3,518,261 mut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…MicroRNAs (miRNAs), which are a class of endogenous small noncoding RNAs, negatively regulate gene expression by inducing translational repression or mRNA decay [ 18 ]. In pancreatic cancer, miRNA dysregulation is associated with a broad spectrum of cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), which are a class of endogenous small noncoding RNAs, negatively regulate gene expression by inducing translational repression or mRNA decay [ 18 ]. In pancreatic cancer, miRNA dysregulation is associated with a broad spectrum of cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are noncoding single-stranded RNAs containing 21∼25 nucleotides, which have a crucial impact in the adjustment of gene representation at the translational level. At present, a number of research results have indicated that the improper expression of miRNAs is closely related with the etiopathogenesis of many cancers. , For example, the maladjusted expression of miRNA Let-7a and miRNA-21 is intensely relevant with early breast cancer . The abnormal expression of miRNA-141 could be an indicator for the development of prostate cancer, and miRNA-155 is closely correlated with cervical cancer .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a family of small noncoding RNA molecules of approximately 20-22 nucleotides in length, are essential to the regulation of multiple biological processes, including gene regulation, apoptosis, and maintenance of cell differentiation (19,20). In particular, miRNAs play a key role in regulating gene expression, and miRNAs are commonly dysregulated in cancer (21,22). In terms of lung cancer, miRNAs can be used as diagnostic and prognostic markers, and have a dual role in indicating carcinogenesis and behavior (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%